SEVERE CONCURRENT BLUNT ABDOMEN TRAUMA: SPECIFIC COURSE OF TRAUMATIC DISEASE (REPORT ONE) - I. M. Sаmokhvаlov; S. V. Gаvrilin; D. P. Meshаkov; S. V. Nedomolkin; V. V. Suvorov; A. V. Denisov; V. Yu. Mаrkevich; T. Yu. Suprun; N. A. Zhirnovа (Вестник анестезиологии и реаниматологии)
The objective: to detect specific features of traumatic disease in those with severe concurrent trauma with a major injury of abdomen organs.Subjects. 326 patients with severe concurrent traumas; the median severity of injury made 4.6 ± 0.1 scores according to Military Field Surgery Score (20.4 ± 0.2 scores as per ISS). 111 patients had severe concurrent abdomen injury (in 52 patients, the severity of abdomen injury prevail over injuries in the other anatomical regions).Results. When analyzing the distribution of variants of the traumatic disease course in 111 patients with a severe concurrent abdomen injury, variant I was observed in 22.5% of patients, variant II – in 47.7%. and variant III – in 29.8%. Among 215 patients with no abdomen injury, variant I was observed in 25.1%, variant II – 46.0%, and variant III – in 28.9%. Thus the distribution of variants of the traumatic disease course among those included into the study was approximately the same. The difference in mortality rates during the first period of the traumatic disease in those injured was not associated with specific features of traumatic disease with abdomen injuries, but for presence or absence of severe brain injury. There were no differences in frequency or duration of the second period of the traumatic disease. In those with severe concurrent trauma and prevailing abdomen injuries, on the average, the time of maximum chances to develop complications is longer with a higher mortality level.Conclusions. In those with severe concurrent trauma and prevailing blunt abdomen injuries, the third period of traumatic disease (time of maximum chances to develop complications) is longer, has a higher statistically significant mortality rate due to a higher frequency of severe sepsis versus patients with same severity of concurrent trauma but with no abdomen injury.